2001
DOI: 10.1530/eje.0.1450241
|View full text |Cite
|
Sign up to set email alerts
|

Bone loss determined by quantitative ultrasonometry correlates inversely with disease activity in patients with endogenous glucocorticoid excess due to adrenal mass

Abstract: Objective: Glucocorticoid excess is widely recognized as one of the most important causes of bone loss. The mechanism of glucocorticoid-induced osteoporosis is presumably multifactorial, and consists of the loss of organic and non-organic compounds. Efforts have been made to develop simple physical methods for the assessment of bone tissue for the screening of subjects at high risk of osteoporosis, without the use of radioactive sources or ionizing radiation. Quantitative ultrasonometry (QUS) has been suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 39 publications
4
48
0
3
Order By: Relevance
“…In recent years, the majority (5)(6)(7)(8)(9)31) but not all (10) cross-sectional studies have suggested that SH is associated with an increased prevalence of osteoporosis. However, only one longitudinal study specifically investigated the rate of spinal and femoral bone loss in female patients with adrenal incidentalomas so far.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the majority (5)(6)(7)(8)(9)31) but not all (10) cross-sectional studies have suggested that SH is associated with an increased prevalence of osteoporosis. However, only one longitudinal study specifically investigated the rate of spinal and femoral bone loss in female patients with adrenal incidentalomas so far.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, if the presence of post-surgical hypocortisolism has to be considered a reliable index of pre-surgical subtle hypercortisolism, it would be expected that the complications of cortisol excess would be more frequent in subjects experiencing post-operative adrenal insufficiency than in those not experiencing it. Indeed, some of the previous cross-sectional studies suggested that also a subtle hypercortisolism may be associated with an increased prevalence of metabolic syndrome and osteoporosis (30)(31)(32)(33)(34)(35)(36)(37)(38)(39), which are common, though not specific, features of overt cortisol excess. However, although the glucocorticoid sensitivity may be different in different tissues (29), it is conceivable that in some patients, this subtle cortisol hypersecretion may be enough to determine end-organ consequences but not to constantly suppress HPA axis function and, therefore, to lead to hypocortisolism after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…They also have a high prevalence of obesity, hypertension, diabetes and insulin resistance. Abnormalities in bone turnover and bone mass have been reported as well (Torlontano et al 1999, Tauchmanova et al 2001, Francucci et al 2002. In a recent study, involving 70 women with AI and 84 controls, evaluated by qualitative CT, the prevalence of vertebral fractures in pre-and postmenopausal AI patients, was significantly higher than in controls (Chiodini et al 2004).…”
Section: Cortisol-secreting Massesmentioning
confidence: 99%